Geomorphological development of mountain Dagestan and some aspects of history of its flora - A. A. Teimurov; Z. S. Abdulchadjieva; M. A. Djamaldinova (Юг России: экология, развитие)
Questions on formation of modern geomorphological structure and flora of Mountain Dagestan are considered.